2021
DOI: 10.1177/09732179211059607
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide for the Treatment of Transitional Neonatal Hypoglycemia: A Systematic Review

Abstract: Background: Neonatal hypoglycemia is widely recognized as a common, preventable cause of brain injury in infants. Early use of diazoxide, which attenuates insulin secretion, is a possible treatment strategy for neonates that fail first-line management of hypoglycemia. Objective: To systematically evaluate the effectiveness and safety of diazoxide compared to placebo or no diazoxide treatment for improving short- and long-term outcomes in neonates born at ≥35 weeks’ gestation who require treatment for transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A systematic review found low certainty evidence from one randomised trial that early use of diazoxide in SGA infants receiving intravenous dextrose for transitional neonatal hypoglycaemia decreased the duration of intravenous fluids and time to full enteral feeding by approximately 2 days. 29 Although there are no apparent adverse effects in this trial, several case series have highlighted a range of possible side effects, including pulmonary hypertension, oedema, heart failure, neutropenia, reopening of the ductus arteriosus and necrotising enterocolitis. 30–33 However, in other reports, serious side effects in otherwise well infants were rare, 16 34–36 suggesting that some of the conditions associated with diazoxide may reflect confounding.…”
Section: Discussionmentioning
confidence: 87%
“…A systematic review found low certainty evidence from one randomised trial that early use of diazoxide in SGA infants receiving intravenous dextrose for transitional neonatal hypoglycaemia decreased the duration of intravenous fluids and time to full enteral feeding by approximately 2 days. 29 Although there are no apparent adverse effects in this trial, several case series have highlighted a range of possible side effects, including pulmonary hypertension, oedema, heart failure, neutropenia, reopening of the ductus arteriosus and necrotising enterocolitis. 30–33 However, in other reports, serious side effects in otherwise well infants were rare, 16 34–36 suggesting that some of the conditions associated with diazoxide may reflect confounding.…”
Section: Discussionmentioning
confidence: 87%
“…Before starting treatment, a cardiac ultrasound should be performed to exclude pulmonary hypertension 24 . Finally, digestive disorders, hirsutism or cardiac disorders are other possible side effects of diazoxide treatment 25,26 . Somatostatin analogues are used as the second‐line treatment for diazoxide‐unresponsive cases of congenital HI.…”
Section: Discussionmentioning
confidence: 99%
“…While low certainty evidence suggests that glucagon may raise BGC in many infants, several concerns remain, especially the high rate of recurrent hypoglycaemia. It remains unclear whether glucagon administration alters the course of metabolic transition and other approaches may be needed to directly address the underlying pathophysiology of transitional hypoglycaemia, particularly dysregulated insulin secretion [5]. It has been speculated that glucagon is less effective in infants with FGR, although this does not appear to be due to reduced glycogen stores [26].…”
Section: Discussionmentioning
confidence: 99%
“…Further, some infants have ongoing episodes of hypoglycaemia despite dextrose treatment, most likely due to failure to adequately suppress insulin secretion, thereby inhibiting hepatic glucose output [4]. Thus, new treatment approaches are needed that target the underlying pathophysiology and promote glycaemic stability [5].…”
Section: Introductionmentioning
confidence: 99%